EVOLUTION OF THE INTERNATIONAL MARKET OF LEASING SERVICES - RYBCHUK, Anatoly; ZHURBA, Igor; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The current stage of the development of the international economy is characterized by the activation of globalization trends, among which one of the most promising forms of international cooperation, which has significant prospects, is international leasing. Today, leasing operations have become an integral part of the development and stabilization of the world economy. The growth and expansion of the global leasing market is a natural fact of the processes of globalization and integration of both production and the financial sphere. If there is a need to modernize the economy, the use of a leasing approach to financing investments plays a significant role. Being one of the most effective types of investment, leasing is widely used in all countries of the world. In developed countries, the total volume of transactions related to leasing has increased 5 times over the past 15 years. Leasing can be attributed to the form of financing investment projects, which has proven itself in global practice as quite effective for enterprises and in general for the deployment of the investment process The article examines the peculiarities and problems of international leasing as an integral part of the development and stabilization of the world economy. It was revealed that the formation and development of the international market of leasing services is connected not only with the intensive development of production activity, but also with the division of labor in the system of global economic relations. An analysis of the functioning of the international leasing market was conducted, which confirms its maximum convenience and flexibility for business development and expansion. It is shown that the growth and expansion of global leasing services is a natural fact of the processes of globalization and integration of both production and the financial sphere. It is noted that despite the global economic crisis, the leasing industry is constantly expanding, and leasing markets are increasing the scope of new business. It has been confirmed that today the world market of leasing services is successfully overcoming crisis situations in the world economy and demonstrates a significant increase in the consumption of leasing services in various regions and countries of the world.